Mental Health in German Paralympic Athletes During the 1st Year of the COVID-19 Pandemic Compared to a General Population Sample - Busch, Aglaja; Kubosch, Eva Johanna; Bendau, Antonia; Leonhart, Rainer; Meidl, Verena; Bretthauer, Berit; Petzold, Moritz Bruno; Dallmann, Petra; Wrobel, Nina; Plag, Jens; Ströhle, Andreas; Hirschmüller, Anja (Frontiers in Sports and Active Living, 2022)
Introduction: The COVID-19 pandemic has huge influences on daily life and is not only associated with physical but also with major psychological impacts. Mental health problems and disorders are frequently present in elite Paralympic athletes. Due to the pandemic situation new stressors (e.g., loss of routine, financial insecurity) have been added. Therefore, the assessment of mental health in athletes during the COVID-19 pandemic is important to identify prevalence of psychological problems and propose countermeasures. Methods: The mental health of German Paralympic athletes was longitudinally monitored (starting in May 2019). The athletes completed the Patient Health Questionnaire 4 (PHQ-4) on a weekly basis and reported stress level, training hours and training load. During the COVID-19 pandemic 8 measurement timepoints (March 2020 to April 2021) were used to reflect the psychological health course of the athletes. In parallel a convenience sample of the general population was questioned about their psychological distress including the PHQ-4. To be included in the analysis, participants of both groups had to complete at least 4 measurement time points. Matching of the para-athletes and the general population sample was prioritized upon completion of the same measurement timepoints, gender and age. Results: 78 Paralympic athletes (40 women, 38 men, age: 29.8±11.4 years) met the inclusion criteria. 78 matched pairs of the general population (40 women; 38 men; age 30.5±10.9 years) were identified. The para-athletes had a significantly (p < .0001) lower PHQ-4 value at each measurement timepoint compared to the matched control group. No significant age or sex differences were evident regarding the symptom burden. Further, in para-athletes no significant and a weak positive correlation was found between decreased training load and PHQ-4 values and stress level, respectively. Reduced physical activity was significantly associated with higher PHQ-4 values in the general population sample. Discussion: Lower PHQ-4 values reported by the para-athletes compared to the general population sample might be based on a higher resilience due to anchoring effects. Nevertheless, adequate support for individuals suffering from severe psychopathological symptoms should be provided for para-athletes as well as for the general population.